Integrasi Pendidikan dan Psikologi dalam Mengatasi Tantangan Pendidikan di Madrasah Ibtidaiyah - Anwar, Zainul; Putro, Khamim Zarkasi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The variation in the needs of different students in the learning process is one of the challenges of education in Islamic elementary schools. This problem can be seen from two perspectives, namely education and psychology. Departing from this problem, this study seeks to find out the importance of the integration of education and psychology in responding to challenges in Islamic elementary schools and to know the concrete benefits of implementing the integration of education and psychology in primary schools. This research method uses qualitative methods with documentation data collection techniques while the analysis technique used is content analysis techniques. The results of the study in this study found that there are practical strategies that can be applied by educational institutions in the implementation of this integration including innovative and inclusive learning, differentiation-based learning and methods. collaboration between teachers and psychologists. However, it is undeniable that there are inhibiting factors that need to be minimized in this implementation including understanding of the integration of education and psychology, limited resources, challenges of coordination and collaboration as well as cultural and social challenges. If you are able to minimize these inhibiting factors, the integration of education and psychology will have a significant impact on students, including better academic development of students, the development of students' skills in the social-emotional aspect, for teachers to be able to understand the development of students better and be able to prosper the participants. study in the context of psychology. So that it can be concluded that with the integration of education and psychology in Madrasah Ibtidaiyah it is able to create students who have academic skills and are psychologically healthy.